Interplay of dopant and polarons in trifunctional semimagnetic semiconductor for supercapacitor applications: Local structure and electronic structure investigations. (April 2023) - Ponnusamy, Rajeswari; Venkatesan, Rajiu; B., KaniAmuthan; S., Selva Chandrasekaran; K., Shalini; Karuppannan, Aravinth; P., Murugan; N.V., Giridharan; Yadav, A.K.; Jha, S.N.; Bhattacharyya, D.; Sivasubramanian, Dhanuskodi
Abstract: Diluted magnetic semiconductors (DMS), fractionally doped by magnetic ions, are peculiar, and a single semiconductor effectively contributes to charge and spin properties for various applications, including data and energy storage. Here, a low temperature assisted co-precipitation method produced a series of Co doped ZnO nanoparticles. After structural characterizations, zinc vacancy defects were realized via the hyperfine signal with g ∼ 1.96 (spin resonance) and the emissions (photoluminescence) at 410 and 465 nm. The synergistic effect among the Co dopant, native, and polaron defects makes the system exhibit enhanced polarization and electrochemical reactions. Magnetization hysteresis curves demonstrate the intrinsic magnetic nature of the materials that are essential for realizing useful polaronic states. As an anode material, 20 at. % Co doped electrode has a higher specific capacitance and superior cycling stability with charge retention above 98 %, which is much higher than the other ZnO-based electrodes and is associated with the polaron-assisted rapid redox reactions. These polarons also stimulate a ferroelectric polarization of 0.28 μC cm −2 via local lattice distortion. All these findings confirm that the Co doped semi-magnetic ZnO system with multifunctionality is adequate for employment in device fabrication as a low-cost, highly stable material. Highlights: Demonstrated the trifunctionalities of Co: ZnO DMS that are highly formulated by the dopant and ionized Zn vacancy defects. FM is originated via the exchange interactions of magnetic polarons and is reduced by antiferromagnetic Co-Co pairing. PL and EPR confirmed the presence of zinc vacancy defects which can trap free carriers for forming the polarons. Pseudo ferroelectricity of 0.28 μC cm -2 is caused by local structural distortion following the formation of hole polarons. Electrode has superior cycling stability where networking of Co-ions and hole polarons prevents structural damage.